Conflicting Coupling of Unpaired Nucleons and the Structure of Collective Bands in Odd-Odd Nuclei - Levon, A.I.; Pasternak, A.A. (Ukrainian Journal of Physics, 2022)
The conflicting coupling of unpaired nucleons in odd-odd nuclei is discussed. A very simple explanation is suggested for the damping of the energy spacing of the lowest levels in the rotational bands in odd-odd nuclei with the ``conflicting'' coupling of an odd proton and an odd neutron comparative to those of the bands based on the state of a strongly coupled particle in the neighboring odd nucleus entering the "conflicting" configuration.